2011
DOI: 10.1186/1756-0381-4-15
|View full text |Cite
|
Sign up to set email alerts
|

Detection of changes in gene regulatory patterns, elicited by perturbations of the Hsp90 molecular chaperone complex, by visualizing multiple experiments with an animation

Abstract: BackgroundTo make sense out of gene expression profiles, such analyses must be pushed beyond the mere listing of affected genes. For example, if a group of genes persistently display similar changes in expression levels under particular experimental conditions, and the proteins encoded by these genes interact and function in the same cellular compartments, this could be taken as very strong indicators for co-regulated protein complexes. One of the key requirements is having appropriate tools to detect such reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…In S. pombe, treatment with geldanamycin increased fbp1 transcription, but the overall expression was 20 % less than the hsp90 (git10) mutation (Alaamery and Hoffman 2008). In addition, there was only about 20 % overlap of targets with altered expression in cells treated with the Hsp90 inhibitor radicicol or containing a deletion in the gene encoding the Hsp90 cochaperone Sba1 (Echeverria et al 2011). It seems likely that many of these effects are due to altered Sgt1 interaction.…”
Section: Hsp90 Interaction With Sgt1 and Cyr1mentioning
confidence: 91%
See 2 more Smart Citations
“…In S. pombe, treatment with geldanamycin increased fbp1 transcription, but the overall expression was 20 % less than the hsp90 (git10) mutation (Alaamery and Hoffman 2008). In addition, there was only about 20 % overlap of targets with altered expression in cells treated with the Hsp90 inhibitor radicicol or containing a deletion in the gene encoding the Hsp90 cochaperone Sba1 (Echeverria et al 2011). It seems likely that many of these effects are due to altered Sgt1 interaction.…”
Section: Hsp90 Interaction With Sgt1 and Cyr1mentioning
confidence: 91%
“…To gain appreciation of how our results compare with transcriptional changes that occur upon general inhibition of Hsp90, we compared the list of genes that displayed altered expression in hsc82-W296A cells with the list of genes affected by Hsp90 inhibition in yeast. A prior study (Echeverria et al 2011) identified 185 genes whose expression changed at least 1.5 log fold either when Hsp90 was inhibited by radicicol and/or when cells contained a deletion in the cochaperone SBA1. A comparison of the two lists showed that only 38, or 20 %, of the genes identified in that study were also affected by hsc82-W296A mutation (Table S3).…”
Section: Hsp90 Interacts With Cyr1 In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some previously identified HSP90 client proteins and interactors were found to be than 23 studies in which higher-throughput, unbiased survey approaches have been taken to detect proteins interacting directly or indirectly with HSP90. These studies have commonly involved genetic, chemical genetic and physical interaction screens performed in yeast [8][9][10][11][12][13][14] as well as large-scale analyses, commonly utilizing affinity purification of HSP90, of proteins present in HSP90 complexes. 7,[15][16][17][18][19][20] Only a few efforts have been made previously toward characterizing the global cellular effects of HSP90 inhibition in mammalian cells.…”
Section: Expanding the Hsp90 Proteome Using Silac Technologymentioning
confidence: 99%
“…Integration of experimental data in protein-protein interaction (PPI) networks to build explorable maps using Cytoscape (http://www.cytoscape.org) has been previously described [29,30]. Briefly, using the human-centred PPI database built by Echeverria et al [31], it was possible to extract a network containing the PPIs between the query proteins and their interactors.…”
Section: Network-based Data Organization and Discoverymentioning
confidence: 99%